Design, synthesis, in silico and antibacterial evaluation of curcumin derivatives loaded nanofiber as potential wound healing agents - Aya Yaseen Mahmood Alabdali; Raghda Khalid; Marwah Kzar; Mohammed Oday Ezzat; Gan Min Huei; Tan Wei Hsia; R. Mogana; H. Rahman; Basma M. Abd Razik; Praveen Kumar Issac; Sasikala Chinnappan; Shaik Ibrahim Khalivulla (Journal of King Saud University: Science, 2022)
Objective: Drug resistance can result in mortality and morbidity due to treatment failures. Therefore, researchers are actively involved in the urgent development of new antibacterial agents which are more effective against drug-resistant bacteria. This study is aimed to prepare curcumin derivatives (CD) nanofiber and test its antibacterial activity by disk diffusion test and evaluate their role in wound healing when potentially binds with transforming growth factor-beta type 1 kinase domain (TGF-β) and Glycogen synthase kinase-3 beta (GSK3-β). Method: Molecular docking and molecular dynamic have been used to select the most potent dual-action molecules on both TGF-β and GSK3-β, most active 2 compounds have been synthesized and characterized by 1H and 13C (NMR), IR spectroscopy, Electrospinning of CD in ethanol were studied by adding Poly vinyl alcohol (PVA) as a polymer. The properties of the CD/PVA solutions measured, morphology of electrospun CD/PVA was tested by Scanning Electrode Microscope (SEM), antibacterial activity of electrospun nanofiber against Staphylococcus aureus (S. aureus) was tested by disk diffusion method.Results and Conclusions: CD nanofiber were synthesized successfully. The results showed that CD were successfully synthesized with good yield (72% and 78%) for compound1 and 2 respectively, Disc diffusion antibacterial test demonstrated an increased inhibition zone from 0.5 to 5.0 mg loaded CD with the largest inhibition zone of 8.5 ± 0.71 and 9.67 ± 0.29 mm for compound1 and 2 respectively. Hence, it can be concluded that these CD/PVA could be a new source in designing new antibacterial wound dressing for diabetic patients.